ANALISIS KEISHIKI MEISHI TOKI, KORO, DAN SAI SEBAGAI SINONIM DALAM KALIMAT BAHASA JEPANG (ANALYSIS OF KEISHIKI MEISHI TOKI, KORO, AND SAI AS SYNONYMS IN JAPANESE SENTENCES) - Mochamad Agung Sutisna; Aep Saeful Bachri; Sudjianto Sudjianto (Jurnal Japanedu: Pendidikan dan Pengajaran Bahasa Jepang, 2016)
Language was born naturally and has word that have “twin meaning” with other words called synonym word (ruigigo). As language which is have a tons of expression, Japanese have so many ruigigo that spreaded in class word including noun, verb, adverb, ect. Especially in class word noun, focus on this research is about to analyse three formality-noun which is not mention the meaning of the word itself but build the meaning of the sentence. The “three” of formality-noun are toki, koro, and sai that have meaning “pada saat” in Indonesia. Purpose of this research is to find, to research the utilities, differences/equality, and to analyse the atmosphere, condition as possibility to replacing each others in Japanese sentence. This research using descriptive analytic research method. This method will find out an equality/difference, utility condition, meaning, and possibility of replace as answer of the problems. The result of this reaserch is toki, koro and sai could translated “pada saat” in Indonesia directly while koro has meaning “sekitar” in Indonesia as well. Density of synonym that showed by three formality-noun toki, koro, and sai make toki could replacing koro and sai in every single condition except when toki accompanying with condition which is sai cannot. In other side, koro and sai has a little chance to be replaceable in sentence because koro and sai have a tons of requirement to replacing each other. All of the substitution have impact to meaning, period, and emphasize of the sentence.